A survey of plants used to treat livestock diseases in the Mnisi community, Mpumalanga, South Africa, and investigation of their antimicrobial activity - McGaw, Lyndy Joy (University of Pretoria, 2026)
Dissertation (MSc)--University of Pretoria, 2018.